“Tobacco Is the Chief Medicinal Plant in My Work”: Therapeutic Uses of Tobacco in Peruvian Amazonian Medicine Exemplified by the Work of a Maestro Tabaquero - Berlowitz, Ilana; Torres, Ernesto García; Walt, Heinrich; Wolf, Ursula; Maake, Caroline; Martin-Soelch, Chantal (Frontiers in Pharmacology, 2020)
Introduction. Harmful usage of tobacco is a public health problem of global concern and, in many countries, the main risk factor for non-communicable diseases. Yet, in the Peruvian Amazon, the geographical region believed to be tobacco's historical birthplace, this plant is associated with a strikingly different usage and repute: Tobacco (especially Nicotiana rustica) in this area is described as a potent medicinal plant, used topically or via ingestion to treat a variety of health conditions. The goal of this transdisciplinary field study was to investigate clinical applications of the tobacco plant as per Amazonian medicine exemplified in the practice of a reputed Maestro Tabaquero, an Amazonian traditional healer whose medical specialization focuses on tobacco-based treatments. Methods. Using a transdisciplinary clinical approach, we conducted in-depth interviews with the tabaquero applying the systematizing expert interview method, in order to map modes of preparation and administration, indications, contraindications, effects, risks, adverse effects, and systemic aspects of tobacco-based remedies. Results. The informant's descriptions revealed refined knowledge on this plant's therapeutic properties and scope, safety profile, and application techniques. The main indications mentioned included "problems of the mind", of the respiratory system, parasitic illnesses (intestinal/skin), gout, and Amazonian epistemic conditions described as spiritual-energetic in nature. A liquid remedy taken orally was his most commonly used preparation, with acute/sub-acute effects involving a pronounced psychoactive component (altered state of consciousness) and physiological response (emesis, nausea). A skilled tabaquero that knows how to dose, administer, and intervene in case of adverse effects was considered imperative for safe treatment delivery. Conclusions. To our knowledge, this is the first study employing a transdisciplinary clinical approach to examine therapeutic applications of tobacco by an Amazonian tabaquero. Our findings significantly contribute to the growing research literature on Amazonian medicine and emergent psychedelic-assisted therapies and could, in the long-term, open new treatment avenues in several domains. Forthcoming studies should assess toxicity/safety and clinical outcomes of patients receiving Amazonian tobacco-based treatment.